Update on Legionnaires’ disease: pathogenesis, epidemiology, detection and control - Hilbi, Hubert (2010)
Legionellosis or Legionnaires’ disease is an emerging and often-fatal form of pneumonia that is most severe in elderly and immunocompromised people, an ever-increasing risk group for infection. In recent years, the genomics of Legionella spp. has significantly increased our knowledge of the pathogenesis of this disease by providing new insights into the evolution and genetic and physiological basis of Legionella–host interactions. The 7(th) international conference on Legionella, Legionella 2009, illustrated many recent conceptual advances in epidemiology, pathogenesis and ecology. Experts in different fields presented new findings on basic mechanisms of pathogen–host interactions and bacterial evolution, as well as the clinical management and environmental prevalence and persistence of Legionella. The presentations revealed remarkable facts about the genetic and metabolic basis of the intracellular lifestyle of Legionella and reported on its striking ability to manipulate host cell processes by molecular mimicry. Together, these investigations will lead to new approaches for the treatment and prevention of Legionnaires’ disease.